A review of existing scientific literature on welfare assessment of farmed species applied in commercial practice: identification of strengths, weaknesses, and areas for further development - de Jong, Ingrid C.; Ouweltjes, Wijbrand; Llonch, Pol; Martin Valls, Gerard E.; Ko, Heng-Lun; Spoolder, Hans; Strappini, Ana C. (Frontiers in Veterinary Science, 2025)
In the last decades, significant progress in welfare assessment of commercially farmed species has been achieved. Since then, various initiatives applied and improved existing protocols, or developed new ones for species like farmed rabbits or fish. This has resulted in a wide range of protocols, indicators and measures potentially lacking standardization and harmonization. However, standardized protocols are crucial for generating quantitative and comparable welfare data. In this literature review we (i) provide the state-of-the-art regarding application of welfare assessment protocols under commercial conditions for farmed species, (ii) their representation of the five welfare domains, and (iii) which animal-based welfare indicators have been applied. Further, (iv) we evaluate the alignment of welfare indicators as applied in scientific publications with highly relevant welfare consequences as defined by European Food Safety Authority (EFSA) for dairy cattle, pigs, broilers, and laying hens. Based on this, we (v) identify strengths and weaknesses regarding the domains covered and use of animal-based indicators, and define areas for further development. Most scientific publications focused on dairy cattle, followed by broilers, pigs and sheep. No publications were found for aquatic invertebrates, insects, fish species other than salmonids, and quails, highlighting the need for welfare assessment protocols for these species. Dairy cattle, horses, and sheep accounted for the highest number of unique indicators. Protocols generally covered all five welfare domains, with health indicators dominating. Animal-based welfare indicators were most prevalent. Common indicators across species were extracted and can be a starting point for the development of assessment protocols for novel species. Highly relevant welfare consequences as defined by EFSA were addressed. In conclusion, while welfare assessment protocols have been developed and tested under commercial conditions for many farmed species, assessment protocols for small-scale farmed species need attention. The wide variety of indicators extracted shows a lack of standardization and harmonization, risking divergence in indicators assessed between protocols. Attention should be given to define standardized welfare indicators per species, enabling comparable data collection related to important welfare issues and benchmarking to improve farm animal welfare.